Pengaruh Net Profit Margin (NPM), Current Ratio dan Debt to Equity Ratio terhadap Dividen Payout Ratio (Suatu Kajian Studi Literatur Manajemen Keuangan Perusahan) - Yohanes Juan Permata Hatul; Henny A. Manafe; Stanis Man (Dinasti Review, 2022)
Abstract: Previous research or appropriate research has a role for research or literature review in order to be able to review the details of each variable that influences or other factors that participate in influencing that variable. This research reviews the factor literature review, specifically related to factors that have an impact on the dividend payout ratio, namely net profit margin (NPM), current ratio and debt to equity ratio. Writing this study intends to be able to determine the hypothesis that gives effect to each variable so that it can be useful for subsequent research. The results obtained in writing this article are: 1) Net profit margin (NPM) has a positive and significant impact on the dividend payout ratio; 2) The current ratio has a positive and crucial impact on the dividend payout ratio; 3) The debt to equity ratio has a positive and crucial impact on the dividend payout ratio; 4) Net profit margin (NPM), current ratio, and debt to equity ratio have a positive and crucial effect simultaneously on the dividend payout ratio. Abstrak: Riset sebelumnya atau riset yang sesuai berperanan bagi riset atau kajian pustaka agar bisa mengulas perihal masing-masing variabel yang memengaruhi ataupun faktor lainnya yang berpartisipasi dalam memengaruhi variabel tersebut. Riset ini mengulas perihal kajian pustaka faktor, terkhusus terkait faktor yang berdampak pada dividen payout ratio, yaitu net profit margin (NPM), current ratio maupun debt to equity ratio. Penulisan kajian ini bermaksud agar bisa menentukan hipotesis yang memberi pengaruh bagi masing-masing variabel agar bisa bermanfaat untuk riset berikutnya. Hasil yang didapat pada penulisan artikel ini ialah: 1) Net profit margin (NPM) berdampak positif maupun bermakna pada dividen payout ratio; 2) Current ratio berdampak positif maupun krusial bagi dividen payout ratio ;3) Debt to equity ratio berdampak positif maupun krusial bagi dividen payout ratio; 4) Net profit margin (NPM), current ratio, dan debt to equity ratio mempengaruhi positif maupun krusial secara simultan bagi dividen payout ratio.